Evaluation of humic acids produced from Pakistani subbituminous coal by chemical and fungal treatments. (15th October 2020) - Sabar, Muhammad Adnan; Ali, Muhammad Ishtiaq; Fatima, Noureen; Malik, Aneela Younas; Jamal, Asif; Liaquat, Rabia; He, Huan; Liu, Fang-Jing; Guo, Hongguang; Urynowicz, Michael; Huang, Zaixing
Graphical abstract: Highlights: The combined fungal and chemical treatments facilitated the coal depolymerization. HPSEC revealed significant effects of HNO3 pretreatment with fungus than H2 O2 . Fungal treatment has produced humic acids with high nitrogen contents. Fungal-transformed humic acids had higher molecular mass. Abstract: The development of bio-processing low rank coal into fuels and non-fuel products has received growing interest in recent years, e.g., production of alternative chemical stock (i.e., humic acids) by the fungal transformation. Previous studies have demonstrated that fungal strains isolated from coal environments can play an important role in the coal-transformation processes with in vivo optimization and chemical pretreatments. In this study, the influence of chemical pretreatments (nitric acid and hydrogen peroxide) with a fungal isolate from coal on the depolymerization of Pakistani subbituminous coal was conducted. The chemical pretreatment exhibited enhanced production of humic acid from 13.5% to 54.2% for nitric acid and 45.7% for hydrogen peroxide. Nitric acid was more effective pretreatment in individual and combination with fungal-mediated depolymerization than hydrogen peroxide. The production of fungal-transformed liquid-derived humic acids were 36.4% and 31.1% for nitric acid and hydrogen peroxide pretreated coal. The results showed that the fungal-transformed humic acid has a high molecular weight, elevated aromatic condensation with mono and poly-substituted functional groups than the chemically treated and raw coal-derived humic acids. The fungal treatment also increased the nitrogen content in the resultant extract, which can be beneficial to the functionality of humic acids. By combining chemical and fungal treatment, it is possible to improve the quantity and quality of humic acids extracted from low rank coal. This is a promising approach in the development of more sustainable-cleaner products from Pakistan's coal resources for the production of bio-active humic acid.